2013
DOI: 10.1016/j.gca.2013.03.043
|View full text |Cite
|
Sign up to set email alerts
|

Influence of chemical weathering on the composition of the continental crust: Insights from Li and Nd isotopes in bauxite profiles developed on Columbia River Basalts

Abstract: Glacial diamictites, with ages ranging from $2900 to 0.01 Ma, record the changing composition of the upper continental crust through time (Gaschnig et al., 2014). Li concentrations and isotopic compositions, combined with Pb isotopic compositions, chemical index of alteration (CIA) values and relative Sr concentrations are used here to assess the degree of chemical weathering recorded in these deposits and the origin of this signature. The d Li values of most of the diamictites (ranging from À3.9 to +3.5) are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
66
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(77 citation statements)
references
References 82 publications
10
66
1
Order By: Relevance
“…This suggests a negligible influence of atmospheric deposits (both dust and rainwater) on the Li isotope composition of regolith. The result is significantly different from previous results showing that there is a significant influence of atmospheric deposits in Hawaii (Pistiner and Henderson, 2003;Huh et al, 2004), or in other basaltic environments (Kisakü rek et al, 2004;Pogge von Strandmann et al, 2012;Liu et al, 2013). The correlation between d 7 Li value and molar Nb/Li exhibited by the Hawaiian soils studied here supports these calculations (Fig.…”
Section: à4contrasting
confidence: 87%
See 2 more Smart Citations
“…This suggests a negligible influence of atmospheric deposits (both dust and rainwater) on the Li isotope composition of regolith. The result is significantly different from previous results showing that there is a significant influence of atmospheric deposits in Hawaii (Pistiner and Henderson, 2003;Huh et al, 2004), or in other basaltic environments (Kisakü rek et al, 2004;Pogge von Strandmann et al, 2012;Liu et al, 2013). The correlation between d 7 Li value and molar Nb/Li exhibited by the Hawaiian soils studied here supports these calculations (Fig.…”
Section: à4contrasting
confidence: 87%
“…7 Li present is close to d 7 Li of the parent rock, despite $30% Li loss by leaching, indicating that during the initial stage of basalt dissolution Li loss is not associated with significant Li isotope fractionation, in good agreement with experimental and other field studies (Pistiner and Henderson, 2003;Huh et al, 2004;Wimpenny et al, 2010a;Verney-Carron et al, 2011;Pogge von Strandmann et al, 2012;Liu et al, 2013). (2) The larger Li losses at the 20 ka and 150 ka sites (s int = À58% and À49%, respectively; Fig Li associated with Li incorporation into secondary phases.…”
Section: Controls Of LI Isotope Fractionation During Basalt Alterationsupporting
confidence: 81%
See 1 more Smart Citation
“…Later, Lundstrom et al (2005) reported diffusive fractionation of Li isotopes in the Trinity Ophiolite. Following this, a series of studies reported Li diffusion within the country rocks adjacent to Li-rich intrusions (Teng et al, 2006;Marks et al, 2007;Liu et al, 2013), finding large and systematic Li isotopic variation over tens of meters and extremely low δ 7 Li (down to −20❤) values, which they interpreted to be the result of diffusion-driven fractionation of Li isotopes. Jeffcoate et al (2007) and Parkinson et al (2007) observed diffusive fractionation of Li isotopes on a grain scale in peridotites and phenocrysts in basalt.…”
Section: Diffusive Fractionation Of LI Isotopesmentioning
confidence: 95%
“…On one hand, Li isotopes can be a powerful tracer of chemical weathering (Chan et al, 1992;Pistiner and Henderson, 2003;Rudnick et al, 2004;Liu et al, 2013;Dellinger et al, 2017). On the other hand, the rapid diffusivity of Li and the associated large kinetic isotopic fractionations make Li a promising geospeedometer for determining rates of rapid geologic processes that can be difficult to determine using other perimental studies (Cherniak and Watson, 2010), which showed that Li can diffuse rapidly in zircon under crustal P-T-X conditions.…”
Section: Introductionmentioning
confidence: 99%